2013
DOI: 10.1002/bjs.9153
|View full text |Cite
|
Sign up to set email alerts
|

Association between operative approach and complications in patients undergoing Hartmann's reversal

Abstract: A laparoscopic approach to Hartmann's reversal was associated with fewer complications than open surgery in this highly selected group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 28 publications
4
44
2
1
Order By: Relevance
“…A more recent systematic review, of over 6000 patients, estimated the risk of operative mortality after ROH to be around 1%, which is in keeping with the results of the present study and comparable with other equivalent major elective colorectal procedures [3,18]. Using similar criteria, a large contemporary North American study [24] reported the prevalence of major morbidity as 13%, a rate similar to that found in the present study. Crude reported morbidity rates range from 3% to 50% [6,8,[19][20][21], a variation that may partly be caused by the inclusion of either all complications or only major complications [16,22].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A more recent systematic review, of over 6000 patients, estimated the risk of operative mortality after ROH to be around 1%, which is in keeping with the results of the present study and comparable with other equivalent major elective colorectal procedures [3,18]. Using similar criteria, a large contemporary North American study [24] reported the prevalence of major morbidity as 13%, a rate similar to that found in the present study. Crude reported morbidity rates range from 3% to 50% [6,8,[19][20][21], a variation that may partly be caused by the inclusion of either all complications or only major complications [16,22].…”
Section: Discussionsupporting
confidence: 90%
“…In an attempt to aid future comparison, we standardized our morbidity reporting using internationally accepted definitions [23]. The largest study yet to examine this question estimated the prevalence of laparoscopic surgery to be 13%, although the authors were unable to report the convertion rate [24]. There has been considerable recent interest in the use of laparoscopic surgery for ROH.…”
Section: Discussionmentioning
confidence: 99%
“…4 The UK, in particular, has a poor reversal rate, being stated as low as 18-22%. 5,6 This rate is extremely low compared with studies in the US that report reversal rates of 37% 7 and in Spain, reporting 35%. 5 Reversal is also associated with high complication and morbidity rates.…”
mentioning
confidence: 81%
“…8,9 Laparoscopic reversal of Hartmann's procedure (LRH) has been associated with a lower postoperative complication rate, a shorter hospital stay and a reduction in morbidity compared with open reversal (ORH). 7,10,11 LRH could therefore offer reduced morbidity and mortality while improving reversal rates as patients are more likely to be fit for laparoscopic surgery. This retrospective case note review aimed to examine the differences between ORH and LRH on patient morbidity and mortality in a single teaching trust.…”
mentioning
confidence: 99%
“…published a systematic review and meta‐analysis of eight retrospective studies comparing laparoscopic with open reversal of Hartmann's procedure. Since this review, five further retrospective studies and one large multicentre study using prospectively collected data extracted from the American College of Surgeons National Surgical Quality Improvement Program database have also been published. These studies have consistently supported the hypothesis that laparoscopic reversal of Hartmann's procedure is associated with fewer post‐operative complications, a lower mortality rate and a shorter length of hospital stay compared with open reversal of Hartmann's procedure.…”
Section: Introductionmentioning
confidence: 99%